1995
DOI: 10.1016/0029-7844(95)00028-p
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flecainide acetate on fetal heart rate variability: A case report

Abstract: Flecainide use can cause the absence of accelerations and poor variability in the FHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…The authors suggested that the mechanism may be an induced activation of sympathetic activity. This seems to be corroborated in a case of fetal SVT treated with flecainide in which the authors note reduced fetal HRV in spite of the presence of documented fetal movement activity 22 . Nonetheless, we found an opposite effect in the male fetus after treatment began, that is, an increase in the time‐domain HRV measures over a 6‐week period.…”
Section: Discussionsupporting
confidence: 86%
“…The authors suggested that the mechanism may be an induced activation of sympathetic activity. This seems to be corroborated in a case of fetal SVT treated with flecainide in which the authors note reduced fetal HRV in spite of the presence of documented fetal movement activity 22 . Nonetheless, we found an opposite effect in the male fetus after treatment began, that is, an increase in the time‐domain HRV measures over a 6‐week period.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to these findings in adults, case reports have been published which describe reduced fetal HRV after prenatal treatment with Flecainide [36,37]. In line with these clinical observations, we found a reduction of shortterm variability at comparable concentrations of Flecainide.…”
Section: Ivabradinesupporting
confidence: 76%
“…Van Geldcr-Hasker et al [6] reported the effect of fle cainide acetate on fetal heart rate variability. They re…”
Section: Discussionmentioning
confidence: 99%